2019
DOI: 10.1111/ajps.12433
|View full text |Cite
|
Sign up to set email alerts
|

Does Direct Democracy Hurt Immigrant Minorities? Evidence from Naturalization Decisions in Switzerland

Abstract: Do minorities fare worse under direct democracy than under representative democracy? We provide new evidence by studying naturalization requests of immigrants in Switzerland that were typically decided with referendums in each municipality. Using panel data from about 1,400 municipalities for the 1991–2009 period, we exploit Federal Court rulings that forced municipalities to transfer the decisions to their elected municipality councils. We find that naturalization rates surged by about 60% once politicians ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 27 publications
(34 reference statements)
0
22
0
2
Order By: Relevance
“…Standard Swiss practice is for citizenship applications to be decided at the municipal level, with procedures for resolving applications varying across municipalities (27,32). Immigrants who…”
Section: Institutional Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Standard Swiss practice is for citizenship applications to be decided at the municipal level, with procedures for resolving applications varying across municipalities (27,32). Immigrants who…”
Section: Institutional Backgroundmentioning
confidence: 99%
“…We base our sample on data collected by (32). They retrieved records of referendums and leaflet information from municipal archives for all immigrants whose naturalization applications were put to public vote in all 46 ballot-box municipalities between 1970 and 2003, when the Swiss Supreme Court struck down the procedure as unconstitutional (27). In total, our sample from the municipal archives contains N = 4, 160 applicants.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Research on direct democracy has examined effects on the size of government (Matsusaka 1995;Funk and Gathmann, 2011), political participation and redistributive spending (Hinnerich and Pettersson-Lidbom, 2010), discriminatory local policies (Hainmueller and Hangartner, 2015), and happiness (Frey and Stutzer, 2005). Using experimental variations similar to those employed in this study, Olken (2010) finds a strong positive effect of the use of direct democracy in Indonesia on villagers' satisfaction, but no effect on the choice of the general project itself, other than a relocation effect of women's projects towards poorer areas.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, this article provides a new theoretical perspective on the relationship between direct democracy and marginalized groups. Some empirical studies have shown that direct democratic procedures tend to produce outcomes that are systematically biased against the interests of socially marginalized groups, such as racial and ethnic minorities (Gamble ; Hainmueller and Hangartner ; Hajnal ). My study indicates that opportunities and experience under direct democracy may create some positive behavioral implications for marginalized groups.…”
mentioning
confidence: 99%